Caribou herds of northwest Alaska, 1850-2000 - Burch, Ernest S., 1938-2010; Krupnik, Igor.; Dau, J. (Jim) (Fairbanks : University of Alaska Press, 2012)
In his final, major publication Ernest S. "Tiger" Burch Jr. reconstructs the distribution of caribou herds in northwest Alaska using data and information from research conducted over the past several decades as well as sources that predate western science by more than one hundred years. Additionally, he explores human and natural factors that contributed to the demise and recovery of caribou and reindeer populations during this time. Burch provides an exhaustive list of published and unpublished literature and interviews that will intrigue laymen and experts alike. The unflinching assessment o.
Appendix 1: Memorandum (E.S. Burch Jr. to Bockstoce, Dau, Hill, Krupnik, and Pratt, February 26, 2010)Appendix 2: Ecoregions of Northwest Alaska by E.S. Burch Jr; Appendix 3: Historical Sources by Ernest S. Burch Jr.; Appendix 4: Sources of Information by Ernest S. Burch Jr.; Appendix 5: Notes on the Consumption of Caribou at Herschel Island During the Whaling Era by E.S. Burch Jr.; Abbreviations; Works Cited; Index.
Includes bibliographical references (pages 153-196) and index.
Master record variable field(s) change: 072, 082 - OCLC control number change
Keywords: Caribou -- Alaska, Northwest -- History; Caribou populations -- Alaska, Northwest -- History; Reindeer -- Alaska, Northwest -- History; Wolves -- Alaska, Northwest -- History; Alaska Natives -- History; Herding -- Alaska, Northwest -- History; Human ecology -- Alaska, Northwest -- History; Mammals -- Alaska, Northwest -- History; Mammal populations -- Alaska, Northwest -- History; Indians of North America -- Alaska, Northwest -- History; Natural history -- Alaska, Northwest; Alaska Natives -- History; Caribou -- Alaska -- History; Natural history -- Alaska; Reindeer -- Alaska -- History; Wolves -- Alaska -- History; NATURE -- Animals -- Mammals; SCIENCE -- Life Sciences -- Zoology -- Mammals; Alaska Natives; Caribou; Caribou populations; Herding; Human ecology; Natural history; Reindeer; Wolves; Alaska, Northwest; Electronic books; History